Kierunki działalności sportowo-oświatowej i kulturalnej Łódzkiego Klubu Sportowego w Drugiej Rzeczypospolitej - Kędzia, Piotr (Biuletyn Historii Wychowania, 2014)
The operations of the Łódź Sports Club in the interwar period are an important part of the history of sport in the city of Łódź, as well as Poland. The Club’s prestige and successes should be chiefly attributed to the athletes’ and the coaches’ commitment, coupled with the activists’ organisational skills. A historical analysis of the Club’s operations indicates that, in addition to training athletes in various disciplines, the establishment was also involved in a wide range of impressive cultural and educational activities. These centred on organising reading rooms, talks, lectures, social meetings and trips as well as promoting patriotic values and the idea of fair play. Hence, the Club’s educational work was channelled into axiological models of sports competition on the one hand, and into propagating education and culture on the other.